2018
DOI: 10.3892/ol.2018.7892
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33a downregulation is associated with tumorigenesis and poor prognosis in patients with hepatocellular carcinoma

Abstract: Abstract. In order to examine the prognostic significance of miR-33a in patients with hepatocellular carcinoma (HCC), total RNA was extracted from 149 HCC biopsies, 36 of which were paired with para-carcinoma tissues, and miR-33a expression was measured by reverse transcription-quantitative polymerase chain reaction. The results demonstrated that miR-33a expression was decreased in HCC biopsies compared with normal liver tissue samples. It was also demonstrated that miR-33a expression was significantly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…4,31 On cellular molecular level, both downregulated expression of mir-33a and up-regulated expression of TRIM14 suggest poor prognosis in patients with liver cancer. 37,38 In the current study, significantly decreased promoter methylation level and increased mRNA expression of AHNAK were shown in liver cancer tissues (all P < 0.05), indicating that AHNAK methylation level can be served as a marker for the diagnosis of liver cancer. Collectively, highly expression of AHNAK is associated with the occurrence of liver cancer, which is helpful to the early detection and diagnosis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…4,31 On cellular molecular level, both downregulated expression of mir-33a and up-regulated expression of TRIM14 suggest poor prognosis in patients with liver cancer. 37,38 In the current study, significantly decreased promoter methylation level and increased mRNA expression of AHNAK were shown in liver cancer tissues (all P < 0.05), indicating that AHNAK methylation level can be served as a marker for the diagnosis of liver cancer. Collectively, highly expression of AHNAK is associated with the occurrence of liver cancer, which is helpful to the early detection and diagnosis.…”
Section: Discussionsupporting
confidence: 53%
“…Although the diagnosis and treatment of liver cancer has been better developed, such as surgical resection and liver transplantation, the survival rate is still disappointing . On cellular molecular level, both down‐regulated expression of mir‐33a and up‐regulated expression of TRIM14 suggest poor prognosis in patients with liver cancer . In the current study, significantly decreased promoter methylation level and increased mRNA expression of AHNAK were shown in liver cancer tissues (all P < 0.05), indicating that AHNAK methylation level can be served as a marker for the diagnosis of liver cancer.…”
Section: Discussionmentioning
confidence: 48%
“…Some of them had already been confirmed to be potential prognostic biomarkers in tumors. 11,[23][24][25] In the present study, we concentrated on miR-142-3p, which had already been proved to be involved in several malignancies. Previous studies have shown miR-142-3p was downregulated in various cancers, such as gastric cancer, cervical cancer, colorectal carcinoma, hepatocellular carcinoma, leukemia, acting as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of miR-92a 25 , miR-221 40 , miR-487a 45 and miR-1468 51 might indicate poor prognosis in HCC. Low expression of miR-33a 63 , miR-122 72 , miR-137 76 , miR-194 90 and miR-940 142 in HCC patients were observed to have unfavorable prognosis. High levels of miR-7/21/107 and low expression of maspin implied poor survival of HBV-related HCC 56 .…”
Section: Acting As Diagnostic and Prediction Markers In Hccmentioning
confidence: 94%